Optimization of Green Marketing to Increase Consumer Awareness and Attitude towards Eco-Friendly Housing in Surakarta - Sumaryanto, S; Paramita Pratita, Mutya; Fikriyatuz Zakiyah, Nadiya; Irma Susanti, Nani; Dwi Wahyudi, Henri (Universitas 17 Agustus 1945 Surabaya, 2025)
Purpose This study aims to investigate how elements such as green perceived value, green products, and environmental concern influence consumer attitudes while examining the role of consumer awareness of green products in promoting environmentally friendly purchasing behavior. Design/Methodology/Approach Data were collected from 111 respondents using convenience and purposive sampling methods. The relationships between green perceived value, green products, environmental concern, green product awareness, and consumer attitudes were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Validity and reliability were assessed through convergent and discriminant validity, while hypothesis testing was conducted using the bootstrapping method. Findings The findings reveal that green perceived value and environmental concern positively influence consumer attitudes toward purchasing eco-friendly housing. However, green product awareness does not significantly moderate these relationships. Low consumer awareness limits the positive impact of green value and environmental concern, underscoring the need for enhanced consumer education to foster pro-environmental purchasing behavior. Originality/Value This study provides a novel analysis of green product awareness as a moderating factor in green marketing and consumer attitudes, focusing on non-subsidized housing in Surakarta. The findings offer valuable insights for developers to create effective marketing strategies and for policymakers to expand green building certification programs and promote the adoption of eco-friendly housing solutions by emphasizing the benefits of environmentally friendly products.